Update on the Joint IMF-WB Multipronged Approach to Address Debt Vulnerabilities. (Policy Papers; Policy Paper, 2020)
Amid rising debt risks in low-income developing countries and emerging markets, the IMF and the WB have been implementing a multipronged approach (MPA) to address debt vulnerabilities. Amplification of debt risks owing to COVID-19 has upped the urgency to implement the MPA and highlights the importance of debt sustainability and transparency for long-term financing for development. At the same time, it should be noted that countries have limited capacities which are further stretched by COVID-19 and that implementation of the MPA by itself may not be sufficient to address debt vulnerabilities and risks from global economic shocks.